Antibiotic susceptibility pattern of Staphylococcus aureus in tertiary care hospital, SRMSIMS, Bareilly, U.P. - Gupta, Vaishali; Pachori, Ravi; Goyal, Rahul Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: S. aureus has been recognized as continuously challenging the clinicians despite the availability of antibiotics from nearly 70 yrs and emergence of various types of antibiotic resistance mechanisms especially to methicillin and vancomycin, which was the theme of this study. The study was to determine the antibiotic susceptibility of Staphylococcus aureus in Tertiary Care Hospital, SRMSIMS, Bareilly and also to determine the current status of Vancomycin susceptibility in our Hospital setup considering E-Test as gold standard. Methods: This study was prospective in design from 1st January 2014 to 31st December 2014 and conducted in the Department of Microbiology, SRMSIMS, Bareilly. All S. aureus strains were screened for vancomycin resistance by Dual strip E- test. Results: Out of 505 Staphylococcus aureus isolates, we found that MRSA, VISA, and VRSA as 80.8%, 0.6% and 0.0% respectively. In cases of MRSA, antibiogram showed sensitivity in the range of 99.4 -100% for glycopeptides, and sensitivity to levofloxacin, chloramphenicol was 77.5% and 65.2% respectively. Conclusions: On evaluation of MIC by E-strips, we found that 17% of MRSA were showing MIC values quite near to the MIC value of VISA. So, these strains may convert to VISA, if the injudicious use of vancomycin antibiotics is not stopped.